PERAN KOMISI YUDISIAL DALAM LEMBAGA PERADILAN DAN PENEGAKAN HUKUM DI INDONESIA - Sri Hartati (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2011)
Judicial commission is an independent institution and born of the demands for reform and to perform reformation the Justice Institute has the function to propose the appointment of Supreme Court Justices and overseeing Supreme Court Justices and Judges in all the judiciary courts under the Supreme Court as referred to in the 1945 Constitution of the Republic of Indonesia. Supervision that is carried out by the Judicial Commission includes preventive to repressive supervisions in order to preserve and uphold the honor, dignity, and conduct of judges. With such that existence and function, the judicial commission holds an important and strategic role in the effort to realize the clean and respectable judiciary, as well as reforming the judiciary and create an independent judiciary, impartial (neutral), competent, transparent, uphold the high-values of justice and truth, and authoritative, capable for upholding the authority of law, the aegis of law, and justice.